2011
DOI: 10.1017/s136898001100200x
|View full text |Cite
|
Sign up to set email alerts
|

Positive impact of a pre-school-based nutritional intervention on children's fruit and vegetable intake: results of a cluster-randomized trial

Abstract: Objective: To assess the short-term impact of a nutritional intervention aimed at reducing childhood overweight in German pre-school children. Design: Using a cluster-randomized study design with waiting-list controls, we tested a 6-month intervention administered once weekly by a nutrition expert consisting of joint meal preparation and activities for children and parents such as tasting and preparing nutritious, fresh foods. At baseline, 6 and 12 months, a parent-completed questionnaire assessed fruit and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(104 citation statements)
references
References 78 publications
(112 reference statements)
0
95
1
1
Order By: Relevance
“…Similar results revealed that waist circumference [73], hip circumference, WHtR and WHR [66] were all negatively associated with increased F & V intake. These effects were not previously reported in studies where these parameters were measured for example in young women aged 18 -28 years [74] or in preschool children 3-6 years old [69]. However, increased in WC, WHR and WHtR was observed with increased fruit intake which was not expected.…”
Section: Discussioncontrasting
confidence: 55%
“…Similar results revealed that waist circumference [73], hip circumference, WHtR and WHR [66] were all negatively associated with increased F & V intake. These effects were not previously reported in studies where these parameters were measured for example in young women aged 18 -28 years [74] or in preschool children 3-6 years old [69]. However, increased in WC, WHR and WHtR was observed with increased fruit intake which was not expected.…”
Section: Discussioncontrasting
confidence: 55%
“…Eight publications reported primary outcomes, of which all indicated significantly positive effects on physical activity and/or diet, but findings regarding BMI were mixed: two found decreases [37,38], two found no impact [39,40], and the remaining did not report anthropometric outcomes [41][42][43][44]. For example, the Romp & Chomp intervention in Australia included health education combined with changes to family day care environments and found a decrease in screen time and increase in active play but did not report anthropometric outcomes [41].…”
Section: Prevention Interventionsmentioning
confidence: 99%
“…Based on the inform a tion avail able, 10 studies were considered to have low risk of bias (Chen et al , 2010(Chen et al , , 2011Gow et al , 2010;Kennedy et al , 2009;Kim et al , 2010;LaChausse, 2012;Luszczynska and Haynes, 2009;Østbye et al , 2012;Rosenkranz et al , 2010;Zask et al , 2012), nine had moder ate risk (Bayer et al , 2009;De Bock et al , 2012;Gentile et al , 2009;Gephart and Loman, 2013;Haire-Joshu et al , 2008;Hoffman et al , 2011;NeumarkSztainer et al , 2009;Siegel et al , 2010;van Wier et al , 2009), and six had high risk (Branscum et al , 2013;Foster et al , 2008;French et al , 2010;Spiegel and Foulk, 2006;Taylor et al , 2007;Warren et al , 2003). Nine studies repor ted random iz a tion by a computer, random number tables, or permuted blocks.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Nineteen of 25 studies repor ted posit ive effects on increas ing fruit and/or veget able consump tion (Bayer et al , 2009;Branscum et al , 2013;Chen et al , 2010Chen et al , , 2011De Bock et al , 2012;French et al , 2010;Gentile et al , 2009;Gephart and Loman, 2013;Haire-Joshu et al , 2008;Hoffman et al , 2011;Kennedy et al , 2009;Kim et al , 2010;LaChausse, 2012;Luszczynska and Haynes, 2009;Østbye et al , 2012;Spiegel and Foulk, 2006;Taylor et al , 2007;Warren et al , 2003;Zask et al , 2012), while five revealed no FV effects (Gow et al , 2010;Neumark-Sztainer et al , 2009;Rosenkranz et al , 2010;Siegel et al , 2010;van Wier et al , 2009). One study detected decreased FV consump tion (Foster et al , 2008).…”
Section: Effects On Fv Consump Tionmentioning
confidence: 99%
See 1 more Smart Citation